Loss-of-function mutations in SPEF2 cause multiple morphological abnormalities of the sperm flagella (MMAF). Issue 10 (31st May 2019) - Liu, Wensheng; Sha, Yanwei; Li, Yang; Mei, Libin; Lin, Shaobin; Huang, Xianjing; Lu, Jinhua; Ding, Lu; Kong, Shuangbo; Lu, Zhongxian
Abstract : Background: Multiple morphological abnormalities of the sperm flagella (MMAF) is a kind of severe teratozoospermia. Patients with the MMAF phenotype are infertile and present aberrant spermatozoa with absent, short, coiled, bent and/or irregular flagella. Mutations in several genes can explain approximately 30%–50% of MMAF cases and more genetic pathogenies need to be explored. SPEF2 was previously demonstrated to play an essential role in sperm tail development in mice and pig. Dysfunctional mutations in SPEF2 impair sperm motility and cause a short-tail phenotype in both animal models. Objective: Based on 42 patients with severe infertility and MMAF phenotype, we explored the new genetic cause of human MMAF phenotype. Methods and results: By screening gene variants in 42 patients with MMAF using whole exome sequencing, we identified the c. 12delC, c. 1745-2A > G, c. 4102 G > T and c. 4323dupA mutations in the SPEF2 gene from two patients. Both of these mutations are rare and potentially deleterious. Transmission electron microscope (TEM) analysis showed a disrupted axonemal structure with mitochondrial sheath defects in the patients' spermatozoa. The SPEF2 protein level was significantly decreased in the spermatozoa of the patients revealed by Western blot (WB) and immunofluorescence (IF) analyses. Conclusion: Our experimental findings indicate that loss-of-function mutations in the SPEF2 gene can cause the MMAF phenotype in human.